THE ACCURACY OF MEDICAL TERMINOLOGY, FRACTURE CODE AND EXTERNAL CAUSE ON SUMMARY FORM PATIENTS - Arini, Liss Dyah Dewi; Sulistyaningrum, Endah; Ifalahma, Darah; Suwanto, Suwanto (jfpublisher, 2022)
Introduction.Writing the main diagnosis on the exit summary sheet must be written based on medical terminology that is precise, clear, and complete, in order to assist coding officers in coding the diagnosis. Based on the initial survey, the inaccuracy of writing medical terminology for fracture diagnosis was 70%. This study aims to determine the accuracy of writing medical terminology on fracture diagnosis on the summary sheet for inpatient discharge. Method.This type of research is a descriptive study, with data collection methods using interviews and observations, as well as a retrospective approach. The sample of this study was 86 which were obtained from 669 populations. Sampling was done by simple random sampling. The research instruments were observation guide, interview guide, work table, ICD-10, medical dictionary, English dictionary, and medical terminology book. Data processing by editing, coding, data entry, tabulation, and data presentation. Data analysis was done descriptively. Results&Analysis.The accuracy of writing medical terminology for the main diagnosis is 22.09%, with 77.91% inaccuracy. The accuracy of writing medical terminology for secondary diagnosis is 66.67%, with inaccuracy as much as 33.33%. Discussion.The author suggests making SOPs related to writing medical terminology, updating guidelines, revising SOP coding and indexing.